2022
DOI: 10.4174/astr.2022.103.3.145
|View full text |Cite
|
Sign up to set email alerts
|

Safety of performing distal pancreatosplenectomy in patients who underwent distal gastrectomy previously: a multicenter cohort analysis with systematic literature review

Abstract: Purpose In patients who have previously undergone subtotal gastrectomy (STG), the remnant stomach is supplied with arterial blood through the splenic artery. It is currently unclear whether the remnant stomach can be safely preserved when performing distal pancreatosplenectomy (DPS) in these patients. Thus, this study aimed to evaluate the safety and feasibility of performing DPS in patients who had undergone a previous STG. Methods A multicenter cohort study was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In the present case, when the right gastroepiploic conduit was resected, only the right gastric artery and vein remained as vessels of the remnant stomach. Previous studies reported successful remnant stomach preservation in patients undergoing distal pancreatectomy following distal gastrectomy despite few stomach vessels [ 25 27 ]. This may be explained by the blood flow from the anastomosed intestinal wall that developed during the interval from the previous gastrectomy, which supports the blood supply to the remnant stomach.…”
Section: Discussionmentioning
confidence: 99%
“…In the present case, when the right gastroepiploic conduit was resected, only the right gastric artery and vein remained as vessels of the remnant stomach. Previous studies reported successful remnant stomach preservation in patients undergoing distal pancreatectomy following distal gastrectomy despite few stomach vessels [ 25 27 ]. This may be explained by the blood flow from the anastomosed intestinal wall that developed during the interval from the previous gastrectomy, which supports the blood supply to the remnant stomach.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported the safety of asynchronous DP in patients who have undergone DG 1,2 . However, there are very few reports on simultaneous DG and DP 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported the safety of asynchronous DP in patients who have undergone DG. 1,2 However, there are very few reports on simultaneous DG and DP. 3 We report a case of simultaneous DG and DP for gastric and pancreatic cancer; this is the first known case of the procedure being robotically performed.…”
Section: Introductionmentioning
confidence: 99%